AniMake Ezzy / Muhammad Ashraf Mohamad Diah - Mohamad Diah, Muhammad Ashraf (2021)
AniMake Ezzy is a new business that provide a service of online animation courses. The main focus and objectives of establishment of AniMake Ezzy is to make sure that anyone who has a dream to learn animation becomes a reality. We realized that the animation course seems can only be learn by people who has a good background and have a proper education. The people that does not have a good financial did not have a chance to register on the animation course because it is usually quite expensive and challenging. Because of that, we are trying to find an alternatives on how to provide an education to everyone that has the intention and determination to learn animation seriously without facing any issues regarding the fees registration. Because of that, AniMake Ezzy have come out with a solution to provide the best training but at the same time offering an affordable prices. We choose to use PowerPoint application software as a platform to create the animation. This application is chosen based on its familiarity and easy to use by most people. We also offer an adjustable timetable where student can choose between the two session that we from Monday to Friday and extra one session on Saturday and Sunday. Only 1 session are needed to be attend for each week which is about 2.5 hours. It means that students can choose the time they are available to attend the classes. Since the start of our first online course intake, we have receive many application for the registration. It is a good sign where are business are on the right track and people are starting to notice the existence of our business. In the future, we are aiming to receive more registration and produce high quality students that are expert in animation.